Breast cancer cells stimulate osteoprotegerin (OPG) production by endothelial cells through direct cell contact - Holen Ingunn; Brown Nicola J; Reid Penny E (Molecular Cancer, 2009)
Abstract Background Angiogenesis, the sprouting of capillaries from existing blood vessels, is central to tumour growth and progression, however the molecular regulation of this process remains to be fully elucidated. The secreted glycoprotein osteoprotegerin (OPG) is one potential pro-angiogenic factor, and clinical studies have demonstrated endothelial cells within a number of tumour types to express high levels of OPG compared to those in normal tissue. Additionally, OPG can increase endothelial cell survival, proliferation and migration, as well as induce endothelial cell tube formation in vitro. This study aims to elucidate the processes involved in the pro-angiogenic effects of OPG in vitro, and also how OPG levels may be regulated within the tumour microenvironment. Results It has previously been demonstrated that OPG can induce tube formation on growth factor reduced matrigel. In this study, we demonstrate that OPG enhances the pro-angiogenic effects of VEGF and that OPG does not stimulate endothelial cell tube formation through activation of the VEGFR2 receptor. We also show that cell contact between HuDMECs and the T47D breast cancer cell line increases endothelial cell OPG mRNA and protein secretion levels in in vitro co-cultures. These increases in endothelial cell OPG secretion were dependent on ανβ3 ligation and NFκB activation. In contrast, the pro-angiogenic factors VEGF, bFGF and TGFβ had no effect on HuDMEC OPG levels. Conclusion These findings suggest that the VEGF signalling pathway is not involved in mediating the pro-angiogenic effects of OPG on endothelial cells in vitro. Additionally, we show that breast cancer cells cause increased levels of OPG expression by endothelial cells, and that direct contact between endothelial cells and tumour cells is required in order to increase endothelial OPG expression and secretion. Stimulation of OPG secretion was shown to involve ανβ3 ligation and NFκB activation.